MEMBANGUN JIWA KEPEMIMPINAN PADA MAHASISWA - Muh. Anwar HM; Faradilla; Umrah; Muh. Taufiq Anugrah (Department of Islamic Education Management, 2023)
A leader is someone who carries out duties and responsibilities, has unique traits, habits, character, personality and characteristics that distinguish him from others and is able to direct, influence someone through attitudes and actions in solving problems in the surrounding environment. Leadership is the ability of a leader to control, lead, influence the thoughts, feelings or behavior of others to achieve goals. The purpose of this study was to determine students' understanding of leadership and how to build the mental character of a leader, using a quantitative descriptive approach research method. While the data analysis technique used is the interval range analysis technique, while the results of research in this journal are the meaning of leadership, the urgency of leadership and shaping the character of a leader from the three indicators after going through a recategorization test, all of which are included in the medium category. implanted early on in every student, students can understand the meaning and urgency of leadership, the formation of a leader's character starting from education, organization and and from family education.